The Influence of Group Therapy on Personal Hygiene Improvement for Grade 7 Students - Rani Ardina; Nuria Muliani (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Efforts need to be made to improve personal hygiene behavior with the end result of reducing the number of infectious diseases. Human IT Middle School Mulia Boarding School is an IT Middle School with a dormitory concept where students live together to improve their religious skills and memorize the Koran. Personal hygiene problems have become commonplace among students. Health education has been done a lot, but not yet effective. One effort that can be done is with a therapy group. Therapy groups can influence other individuals to improve better behavior. This study uses a quasi-experimental design. This study used a purposive sampling technique in selecting subjects. The technique used to collect data is interview. This research will be conducted in July 2022, Islamic Boarding School at Insan Mulya Pringsewu Lampung. This research has received ethical recommendations from KEPK Muhammadiyah University of Pringsewu. Data analysis used the T test. The purpose of this study was to determine the effect of group therapy on improving the personal hygiene of 7th grade students of SMP IT Insan Mulia Islamic Boarding School. The results showed that the average increase in personal hygiene of students in the intervention group was higher than that of the control group (32.15 ± 14.65; 11.30 ± 9.32). The results of statistical tests showed that there was a significant effect of the therapy group on improving the personal hygiene of grade 7 students at SMP It Insan Mulia Boarding School (p value = 0.000). It is recommended to do group activity therapy for students to improve students' personal hygiene.